Activation of X-Succinate Synthases for Fumarate Hydroalkylation Using an In Vitro Activation Method - Anshika Vats; Shukurah Anas; Ankush Chakraborty; Jian Liu; Jimyung Ryu; Sara Mann; Mary Andorfer (Bio-Protocol)
X-succinate synthase enzymes (XSSs) are a class of glycyl radical enzymes (GREs) that play a pivotal role in microbial anaerobic hydrocarbon degradation. They catalyze the addition of hydrocarbons to fumarate using a protein-based glycyl radical, which must first be installed by a radical S-adenosylmethionine (rSAM) activating enzyme (AE). Once activated, XSS enzymes can undergo multiple catalytic cycles, forming C(sp3)–C(sp3) bonds with high stereoselectivity—a feature that highlights their potential as asymmetric biocatalysts. Due to the insolubility of XSS-AEs when heterologously expressed in Escherichia coli, studies have relied on in vivo radical installation protocols. Although these methods have illuminated fundamental details of XSS mechanisms, the inability to install a glycyl radical in vitro has limited biochemical studies and biotechnological advances using these enzymes. Here, we describe an in vitro protocol for reconstituting the activity of benzylsuccinate synthase (BSS), an XSS that catalyzes the addition of toluene to fumarate to form R-benzylsuccinate. To enable in vitro glycyl radical installation, we identified a soluble homolog via genome mining: 4-isopropylbenzylsuccinate synthase activating enzyme (IbsAE). IbsAE was expressed in E. coli and anaerobically purified in moderate yields (6–8 mg of protein per liter of culture); herein, we outline the expression and anaerobic purification of both IbsAE and BSS proteins. We describe a reproducible method for in vitro glycyl radical installation using these recombinant proteins and provide guidance on quantifying radical formation. Our optimized protocol consistently achieves 30%–50% radical installation, comparable to other in vitro GRE activations. Lastly, we demonstrate the application of this protocol for in vitro hydroalkylation reactions, achieving high assay yields (89%–97%). This protocol enables biochemical experiments that were previously challenging using cell extracts and accelerated advancements in XSS engineering and use in biocatalysis.